Push-Pull-Mooring in Consumer Action: Cognitive, Social, and Emotional Factors in Boycotting Pro-Israel Products - Lutfia Izdhihar Qotrunnada; Zakky Fahma Auliya (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study aims to analyze the drivers of brand switching behavior toward pro-Israel fast-moving consumer goods (FMCG) among Generation Z in Indonesia, employing the Push-Pull-Mooring (PPM) framework to examine the roles of cognitive, social, and emotional factors.Method: A quantitative research design was employed, utilizing an online questionnaire to collect data from 200 independent-living Generation Z respondents in the Solo Raya region, who had switched from affiliated to non-affiliated brands. The data were analyzed using multiple linear regression in SPSS version 26.Result: The findings indicate that Product Knowledge (push) and electronic Word-of-Mouth (e-WOM) (pull) are the primary drivers of consumer brand switching. Conversely, Brand Commitment (mooring) emerged as the primary inhibiting factor that significantly prevents consumers from switching to another brand.Practical Implications for Economic Growth and Development: The findings suggest a consumer-driven market realignment with direct implications for economic development. This shift offers substantial opportunities for local and non-boycotted brands to capture market share, thereby stimulating domestic industrial growth, enhancing product diversification, and fostering a more self-reliant national economy. Concurrently, it pressures multinational corporations to adopt more socially responsible and transparent business practices to maintain competitiveness.Originality/Value: This study provides novel insights by being among the first to apply the PPM framework within a politically and ethically charged boycott context in the FMCG sector, bridging the critical gap between switching intention and actual behavior while uniquely integrating the psychological mooring of brand commitment, the cognitive push of product knowledge, and the digital pull of e-WOM.